Developing a new self-harm assessment tool with and for autistic adults - Newell, Victoria (2025)
Research indicates that autistic individuals and those with high autistic traits are more likely to self-harm than non-autistic individuals. However, it remains unclear which, if any, self-harm assessment tools are available to assess self-harm in autistic adults. As a result, researchers and service providers struggle to accurately identify these difficulties and recommend appropriate support and treatment.